S100A14 protein as diagnostic and prognostic marker in hepatocellular carcinoma - Basma Fathy Mohamed; Waleed Mohamed Serag; Reda Mahamoud Abdelal; Heba Fadl Elsergany (Egyptian Liver Journal, 2019)
Abstract Background Protein S100A14 has recently been implicated in the progress of several types of cancers. This study aimed to investigate the clinical significance of S100A14 in the diagnosis of hepatocellular carcinoma (HCC). Results S100A14 was significantly elevated in the HCC group. A cut-off value for serum S100A14 between the HCC group and cirrhosis group is > 0.47 with a sensitivity of 100% and specificity of 88.57%. S100A14 level was a significant diagnostic factor for HCC and a good reference for HCC progression. Conclusion These results suggest that S100A14 is a good diagnostic marker for HCC.